2020
DOI: 10.21203/rs.3.rs-23501/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cross-Sectional Study on Oyo State Health Care Workers Knowledge, Attitude and Practice Regarding Corona Virus Disease 2019(COVID-19)

Abstract: Background Health workers are at the front line of the COVID-19 outbreak response and as such are exposed to hazards that put them at risk of infection. Poor knowledge among HCWs and inadequate infection control practices may lead to the increased risk of COVID-19 nosocomial transmission. This study assessed the knowledge, attitude and practice of Oyo state health care workers on COVID-19 as part of emergency preparedness. Methods A hospital based cross-sectional survey was conducted in selected health facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 2 publications
6
32
4
Order By: Relevance
“…Occupation, educational level, and senatorial zone were signi cantly associated with knowledge level, so also were occupation, educational level, senatorial zone and knowledge level signi cantly associated with attitude; COVID-19 related practices were signi cantly associated with age, senatorial zone and knowledge level. The ndings of this study regarding demographic variables associated with KAP towards COVID-19 are partially comparable to those found in previous studies [14,15,18,19]. Also, our study revealed a signi cant association between knowledge level with attitude and COVID-19 related practices-similarly reported by an earlier study in Iran [15].…”
Section: Discussionsupporting
confidence: 90%
“…Occupation, educational level, and senatorial zone were signi cantly associated with knowledge level, so also were occupation, educational level, senatorial zone and knowledge level signi cantly associated with attitude; COVID-19 related practices were signi cantly associated with age, senatorial zone and knowledge level. The ndings of this study regarding demographic variables associated with KAP towards COVID-19 are partially comparable to those found in previous studies [14,15,18,19]. Also, our study revealed a signi cant association between knowledge level with attitude and COVID-19 related practices-similarly reported by an earlier study in Iran [15].…”
Section: Discussionsupporting
confidence: 90%
“…Data were collected online using a structured questionnaire and using email and telegram services of HWs working in different units of hospitals and HCs. The questionnaire was designed using Google Forms (via docs.google.com/forms ) by referring to former studies on IP and the WHO IP guidelines [ 15 , 16 , 18 , 23 , 26 , 29 ]. The questionnaire consists of questions related to demographics, information sources, risk assessment, knowledge and practice towards the COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…This study found that a shortage of PPEs (facemasks, and glove) and scarcity of hand cleaning solutions (alcohol, and sanitizer) had the main militating factors. These ndings also are shown in studies conducted elsewhere [28][29][30][31][32][33][34][35]. These are evidence that if the health professionals do not get enough amount of PPEs, they are obligated to do the procedures or come in contact with patients with available resources, and a breach in standard precautions inevitable.…”
Section: Comparison and Contrast With Exiting Evidencementioning
confidence: 67%